Pengaruh Model Talking Stick Berbantuan Media Smart Box Terhadap Hasil Belajar PPKN Siswa Kelas III - Safira, Nanda Okta; Sukasih, Sri (Universitas Muhammadiyah Magelang, 2026)
This study aims to determine the effect of using the Talking Stick learning model, Smart Box media, and a combination of the Talking Stick model assisted by Smart Box media on the learning outcomes of Pancasila and Civic Education (PPKn) for third-grade students at SD N Sriwungu. This study used a quantitative research approach with a pre-experimental type of research, namely a one-group pretest-posttest design. The population in this study consisted of 24 students in the third grade of SD N Sriwungu with a saturated sampling technique, namely all members of the population in that class were used as research samples. Data collection was conducted through tests (pre-test and post-test) and learning outcome questionnaires. Data analysis was performed using SPSS version 27.0 through validity testing, reliability testing, Shapiro-Wilk normality testing, and hypothesis testing using the Paired Sample t-test. The results of the study show that the average pretest score of the students was 36.62. After the learning process, the average posttest score increased to 57.70. The normality test results show that the data is normally distributed with a significance value of 0.153 for the pretest and 0.184 for the posttest (>0.05). The hypothesis testing results using the Paired Sample t-test showed a significance value (2-tailed) <0.001 (<0.05), so H₀ was rejected and Hₐ was accepted. This shows that the use of the Talking Stick model assisted by Smart Box media has a significant effect on improving the learning outcomes of third-grade students at SD N Sriwungu. Thus, the Talking Stick model combined with Smart Box media can be an effective learning alternative to improve student learning outcomes.